2014
DOI: 10.3389/fonc.2014.00039
|View full text |Cite
|
Sign up to set email alerts
|

Biotensegrity of the Extracellular Matrix: Physiology, Dynamic Mechanical Balance, and Implications in Oncology and Mechanotherapy

Abstract: Cells have the capacity to convert mechanical stimuli into chemical changes. This process is based on the tensegrity principle, a mechanism of tensional integrity. To date, this principle has been demonstrated to act in physiological processes such as mechanotransduction and mechanosensing at different scales (from cell sensing through integrins to molecular mechanical interventions or even localized massage). The process involves intra- and extracellular components, including the participation of extracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 81 publications
1
44
1
Order By: Relevance
“…We found growth in cell cluster occupancy, but density tended to decrease over time, meaning that cluster generation processes like cell migration and cluster division were underrepresented compared to cell cluster growth, death and detachment processes. Additionally, contrary to expectation, we observed that cell cluster density and occupancy were reduced with increasing stiffness 1,7 . Compared to the permissive characteristics of the low stiffness hydrogels, high stiffness equals a restrictive ECM, which apparently hinders initial cell migration and growth.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We found growth in cell cluster occupancy, but density tended to decrease over time, meaning that cluster generation processes like cell migration and cluster division were underrepresented compared to cell cluster growth, death and detachment processes. Additionally, contrary to expectation, we observed that cell cluster density and occupancy were reduced with increasing stiffness 1,7 . Compared to the permissive characteristics of the low stiffness hydrogels, high stiffness equals a restrictive ECM, which apparently hinders initial cell migration and growth.…”
Section: Discussioncontrasting
confidence: 99%
“…It is also a transport medium for mechanical forces to the basal membrane through integrins that support the tissue tensegrity system, activating cellular genetic and epigenetic mechanisms1 . ECM alterations result in loss of functions such as cell denervation 2 , loss of regeneration and wound-healing capacity3 , loss of the substrate that provides a correct immune response to infectious 4 , tumoral5 and toxic agents6 and alteration of mechanical transmission (mechanotransduction changes)7 . 2D cell culture has been one of the most commonly used in vitro models for biomedical research, due to its ease of use and low cost; however, it is less effective in reflecting the effect of the ECM and potential cellular microenvironment interactions, being unable to capture the interaction between 3D architecture of cells and ECM8 .…”
mentioning
confidence: 99%
“…Concurrently, this same “conduit” facilitates cell-induced tissue remodeling, such as in the case of ECM alignment, due to cytoskeleton dependent cell contraction [43,48]. These intracellular and extracellular events allow cells to mechanically and biochemically “sense” the changing environment thereby effectively addressing the dynamic needs of the tissue.…”
Section: Desmoplastic Sdrmentioning
confidence: 99%
“…while also influencing ECM assembly [43,48,78-81]. Collectively, this posits that the “cytoskeletal conduit” functions as the principal mechano-driver by which cell-induced ECM remodeling and ECM-regulated cellular behaviors are conveyed [20,43,48,82]. A prime example of the influence imparted by this cytoskeletal conduit can be perceived during the nuclear translocation of myocardin-related transcription factor A (MRTF-A).…”
Section: Desmoplastic Sdr: Cancer-associated Fibroblasts-ecm Interactmentioning
confidence: 99%
“…Biotensegrity is also gaining momentum within the scientific community who examine the dynamic behaviour of cells and their interactions with the surrounding extracellular matrix and fascia (Ingber et al 2014;Reilly and Ingber, 2018), thus increasing our understanding of cancer and other illnesses (Tadeo et al 2014). It underpins new ideas about joint mechanics (Levin and Madden, 2005;Hakkak et al 2015) and the global connectivity between these tissues and the nervous system, all of which operate synergistically in controlling movement and are far more than collections of anatomical 'bits' (Profeta and Turvey, 2018;Cabe, 2019).…”
Section: The Conundrummentioning
confidence: 99%